PENGARUH RETURN ON ASSET, RETURN ON EQUITY, NET PROFIT MARGIN, DAN EARNING PER SHARE TERHADAP HARGA SAHAM - Rini Tesniwati; Sriyanto Sriyanto; Ira Windarti; Fadia Rakhmita (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The capital market is one of the sources of external funding for a company. Investors who want to invest in the capital market will analyze the financial ratios owned by a company to determine the financial performance of the company. Food and beverage companies are one of the sectors that are quite attractive to investors to invest. The purpose of this study was to determine the effect of Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Earning Per Share (EPS) on Stock Prices in Food and Beverage Companies Listed on the Indonesia Stock Exchange Period 2017 – 2021. The data used is secondary data in the form of financial statements of food and beverage companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sampling technique used in this study is purposive sampling. The sample used in this study were 10 companies. The data analysis techniques used are normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, coefficient of determination (R2), t test and F test. The test tool used is SPSS Version 25. The results of this study indicate that partially Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Earning Per Share (EPS) affect the stock prices of food and beverage companies listed on the Indonesia Stock Exchange in the period 2017 – 2021. Simultaneously Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Earning Per Share (EPS) affect the stock prices of food and beverage companies listed on the Indonesia Stock Exchange for the 2017 period – 2021.